Battery-less piezoelectric RF remote control system - Sim, Darius (2013)
The 21st Century has seen an increased utilisation of non-renewable energy sources such as fossil fuels to supply up to 80% of our global energy consumption[1]. Global fossil fuel reserves are near depletion and the continual production and use of such hydrocarbon products give rise to environmental issues. As such, alternative energy sources are vital towards alleviating the energy needs of the future.